Customer satisfaction in the restaurant industry: an examination of the transaction-specific model - Andaleeb, Syed Saad; Conway, Carolyn (© 2006 Emerald Group Publishing Limited, 2016)
This article was published in the Women in Management Review [© Emerald Group Publishing Limited] and the definite version is available at : http://dx.doi.org/10.1108/08876040610646536 The Journal's website is at: http://www.emeraldinsight.com/doi/abs/10.1108/08876040610646536